Pengaruh Upah Sistim Bagi Hasil (Profit Sharing) Terhadap Loyalitas Karyawan (Studi Kasus Rumah Makan Kotabuana Pekanbaru) - Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2017)
This study aims to analyze the effect of wages (compensation) profit sharing system to employee loyalty by the object of research at Kotabuana Restaurant Pekanbaru. This research uses census sampling technique to 87 employees. The result of analysis by using simple linear regression obtained by regression equation: Y = 44,172 + 0,157X + ?. Obtained by value for constant of Employee Loyalty sharing is 44.172 when value of profit sharing variable declared as ZERO  and every increase in the value of profit sharing one unit it will affect the increase in employee loyalty of 0.157 units. The result of t test shows that profit sharing has no significant effect on employee loyalty with the result of calculation that t value of profit sharing (X variable) = 1,229 <t table 2,108, and value r_square (coefficient of determination) equal to 0,017, with meaning of profit sharing variable contributed influence to employee loyalty of Restaurant Kotabuana only equal to 17,% and the rest equal (100% -17%) = 83% influenced by other factors